Effect of Yoga Training on Physical Fitness and Balance in Elderly Females - Masoumeh Koohboomi; Ali Asghar Norasteh; Nader Samami (University of Social Welfare & Rehabilitation Sciences, 2015)
Objectives: Senility and reduction of physical activities usually cause undesirable physical and even mental effects on the adults. Since physical activities can improve physical even mental condition, and consequently bring about more independence for adults, the purpose of this paper was to find out the effects of some of yoga practices on some factors of physical preparation in the elderly. Methods & Materials: A total of 45 elderly women (age: 64±6.12 y, height: 162.50±10.21 cm, weight: 63.21±9.71 kg), all enjoying general health were selected through convenience sampling method to take part in this test. In this study, the Sharpened Romberg test (with open and closed eyes), acquiring operation test, timed up and go (TUG) test, number of arm flexion for 30 seconds test, number of takeoff and landing chair, getting hands together from behind, number of sitting and rising of the chair test, were used for measuring the static balance, dynamic balance, agility, upper organ, strength of lower organ, inflection of upper organ, trunk and lower organ, respectively. These tests were performed before and after the program. Data analysis was performed by variance analysis test and t relevant (at significant level P). Results: Research findings showed that yoga exercises for 6 weeks significantly affected the static and dynamic balances with eyes open and closed, agility, upper and lower extremity muscle strength, flexibility, upper and lower extremities. Conclusion: Yoga (Hatha yoga) may have positive effects on physical fitness of the elderly. These effects include improving strength in the upper and lower extremity, static and dynamic balances, and agility.